Studying The Spreading Of Genus Saprolegnia In Waters Of Diwaniyah Province And Characterization The Molecularly - Mohammed Azooz Al-Zamli, Muataz; Kadhim Aboud, Majid (Al-Qadisiyah Journal of Pure Science, 2018)
The present study is concerned with isolation and identification of some aquatic fungi, including its species of Saprolegnia in the waters of Al-Diwaniyah province and molecular characterization. The study is regarded as the first in Iraq according to the information available to us. Two species, Saprolegnia parasitica and Saprolegnia ferax, have been isolated from rivers, lakes and fish. The physical and chemical environmental characteristics have been measured. The types above have been examined to extract the DNA. The (PCR) technique has been used to examine the presence of proteases enzyme. The results of isolation and identification showed that the percentage of the two types were 64% in rivers areas 40% in the lakes areas and 50% in fish. The rates represented the examined samples which were 60 samples. The S. parasitica species is more apparently found during (February, 2014), the number of samples was 12, the less presence of this species in (April, 2014), where the number of sample, was 3. The S. ferax species is more apparently presented in (February, 2014), the number of samples was 10. The less presence was in (April, 2014), the number of samples was 2. The results showed that the number of isolation of Saprolegnia species in study area was 6 in rivers, 2 in lakes, and 3 in fish. The second species, S. ferax showed number of isolations which were 10 in rivers, 8 in lakes, and 2 in fish. The PCR examination has used to detect the rDNA gene which responsible for proteases gene and whether it is found in the two species of fungi. The express way has been used to extract DNA and according to the instructions of manufacturer company. The concentrations of DNA in first species were 121.8-73.0 mcg/microliter and purity 1.87-1.80 .In the second species the concentrations of DNA were 2360.4-166.9 mcg/microliter and purity 2-1.75. The standard rate according to the instructions of company is 1.8, this has been measured by using the Nanodrop Spectrophotometer and reading the absorbing with wave length 260-280 nm and the efficiency of method used and molecular confirmation for fungi species and the determination of fungi species according to the sources of fungi isolation, which one of them is more spread in the study area and which one is more infections for fish. The S. parasitica species was less spread in rivers with percentage of 66.6%. And the percentage of the in lakes and fish was 100%. The second species S.ferax was more spread in rivers with percentage of 70%.The percentage of the in lakes 62% and fish was 100%. The results, by using PCR technique, showed that the percentage of protease in first species was 25% in rivers. In lakes and fish was 100% .Concerning the second species, the percentage of enzyme was 42% in rivers, 40%in lakes, and 50% in fish. It can be concluded that there is a diversity in fungi species with respect to study areas and enzyme secretion in the stages of fungi infection. The enzyme is more apparently found in S.parasitica species compared with S.ferax species.